Heart Transplantation in Patients Older than 65 Years: Worthwhile or Wastage of Organs? - Prieto, David; Correia, Pedro; Batista, Manuel; de Jesus Antunes, Manuel (The Thoracic and Cardiovascular Surgeon, 2015)
Background Patients older than 65 years have traditionally not been considered candidates for heart transplantation. However, recent studies have shown similar survival. We evaluated immediate and medium-term results in patients older than 65 years compared with younger patients.Methods From November 2003 to December 2013, 258 patients underwent transplantation. Children and patients with other organ transplantations were excluded from this study. Recipients were divided into two groups: 45 patients (18%) aged 65 years and older (Group A) and 203 patients (81%) younger than 65 years (Group B).Results Patients differed in age (67.0 ± 2.2 vs. 51.5 ± 9.7 years), but gender (male 77.8 vs. 77.3%; p = 0.949) was similar. Patients in Group A had more cardiovascular risk factors and ischemic cardiomyopathy (60 vs. 33.5%; p < 0.001). Donors to Group A were older (38.5 ± 11.3 vs. 34.0 ± 11.0 years; p = 0.014). Hospital mortality was 0 vs. 5.9% (p = 0.095) and 1- and 5-year survival were 88.8 ± 4.7 versus 86.8 ± 2.4% and 81.5 ± 5.9 versus 77.2 ± 3.2%, respectively. Mean follow-up was 3.8 ± 2.7 versus 4.5 ± 3.1 years. Incidence of cellular/humoral rejection was similar, but incidence of cardiac allograft vasculopathy was higher (15.6 vs. 7.4%; p = 0.081). Incidence of diabetes de novo was similar (p = 0.632), but older patients had more serious infections in the 1st year (p = 0.018).Conclusion Heart transplantation in selected older patients can be performed with survival similar to younger patients, hence should not be restricted arbitrarily. Incidence of infections, graft vascular disease, and malignancies can be reduced with a more personalized approach to immunosuppression. Allocation of donors to these patients does not appear to reduce the possibility of transplanting younger patients.
Keywords: transplantation; heart; heart failure; surgery; complications